Different saturated and monounsaturated fatty acids levels in fish oil-free diets to cobia (Rachycentron canadum) juveniles: Effects in growth performance and lipid metabolism - Marques, Victor H.; Moreira, Renata G.; Branco, Giovana S.; Honji, Renato M.; Rombenso, Artur N.; Viana, Maria Teresa; Mello, Paulo H. de [UNESP]; Mata-Sotres, Jose A.; Araujo, Bruno C. (Elsevier B.V., 2021)
This study aimed to investigate the influences of alternative lipid sources rich in saturated and monounsaturated fatty acids (SFA and MUFA) supplemented with long-chain polyunsaturated fatty acids (LC-PUFA) on production performance and lipid metabolism of Rachycentron canadum (cobia) juveniles. An 8-week feeding trial was carried out using four isoproteic and isolipidic diets as follows: FO-D (fish oil, as control diet), SFA-D (rich in SFA), MIX-D (same levels of SFA and MUFA), and MUFA-D (rich in MUFA). Experimental diets were supplemented with arachidonic acid (ARA), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA) (3, 5, and 10 g kg(1), respectively). The growth performance, fatty acid (FA) profile of liver and muscle, hepatocyte morphology, and gene expression related to the FA synthesis and oxidation on the liver were examined. In general, production performance was not impaired in fish-fed FO-free diets, supporting the hypothesis that alternative lipid sources could be used in cobia's aquafeed formulations when the LC-PUFA are adequately supplemented. High dietary SFA levels were disproportionally deposited the liver and muscle. Contrariwise MUFA was mainly deposited in the liver and muscle, reflecting the dietary inclusion levels. The main FA influencing this pattern were 12:0 and 18:1n-9. The expression of fatty acid synthase (fas) was up-regulated in the FO-D group compared to SFA-D and MIX-D groups. There were no differences in the relative expressions of carnitine palmitoyltransferase 1 (cpt-1 alpha) and lipase lipoprotein (lpl). The liver morphology results indicated that fish-fed SFA-D presented a smaller lipid vacuoles area than those fed other experimental diets. This study shows that SFA with shorter carbon chains such as 12:0 can be administered in cobia aquafeeds to stimulate these molecules' catabolism, providing energy for growth, and retaining LC-PUFAs in tissues, especially in the muscle, exhibiting a healthier fillet for consumers.
Keywords: Fatty acids; Alternative lipids; SFA; MUFA; beta-Oxidation